(untitled) (Quinto Sol, 2011)
This article goes through the modality of internal divisions that exhibited the peronism party from Mendoza throughout general elections in 1973. When the elections were won by the peronist Alberto Martínez Baca, a series of intern conflicts appeared in the winning party that damaged the state administration of public affaires. The internal struggle between the different sectors that makes up the peronism was solved with a political court judgment to the governor. This institutional solution differed from the ones taken in other provincial contexts. Through the analysis of the arguments of the court judgment and the strategies of the defense and the prosecution, the article searches to restore the itinerary of mendocinian peronism, focusing in its heterogeneity of perspectives and points of view, and also approaching the diversity of actors and social sectors that had endorsed to the peronism project.